Effect of Temperature on the Rheological Properties of African Yam Bean (Sphenostylis Stenocarpa) Seed Flour - Igwe, Jeremiah Friday; Eze, John Ikechukwu (Journal of Food Technology Research, 2022)
The effect of temperature on the Rheological properties of African yam bean (Stenostylisstenocarpa) was investigated. The samples were Sorted, washed, and boiled at temperatures of 800C, 1000C, and 1200C respectively. The flour was fluidized and used for the evaluation of the volumetric and mass flow rates. The values of the volumetric and mass flow rates obtained were 81.68±0.8, 89.38±0.16 and 84.69±0.82cm3/g and 45.5±1.02, 43.79±0.03, 46.02±0.88g/s for the temperatures of 800C, 1000C, and 1200C respectively. Data obtained from the stress and strain analysis were 484.38, 554,835.36, and 483,654.28N/m2 respectively while strain was 0.00644, 0.0837, and 0.197. The viscosity had values of 7.568×103, 6.625×107, and 2.455×107 Cp, and ductility values were 6.4%, 72.72%, and 100% respectively. It was observed that the viscosity increased with an increase in temperature to 1000C, and decreased slightly at the temperature of 1200C. The stress had its maximum value at 1000C, but the strain increased linearly. There were fluctuations in the values for the volumetric and mass flow rates respectively. These showed that the temperature affected the Rheological properties of African yam bean seed/flour.